Impact of nutritional quality on mental well-being in obese female: a systematic review - Ramchandani, Dina (International Journal Of Community Medicine And Public Health, 2025)
This systematic literature review explores the bearing of nutrition quality on the overall mental well-being of obese female aged 15-29 years. Thus, the increasing ubiquity of obesity and its related mental health challenges, this study examines the connection between dietary habits and mental health outcomes. This systematic literature review, inclusion criteria include Overweight/obese female youth aged 15-29 years with no prior diagnosed mental health conditions and exclusion criteria includes Participants with chronic physical illnesses, current medication for mental health (MH), or those following specialized diets. The finding suggest that females aged 15-29, particularly in low- to middle-income regions, show poor nutritional habits similar to those in industrialized nations, with a high intake of processed foods, and sugary beverages, and fast food. These dietary choices, coupled with a notable deficiency in essential nutrients (e.g., 78.8% in vitamin D, 34.4% in vitamin B12), contribute to increased obesity rates and related health risks. Obesity in these females is also linked to a greater incidence of MH issues, with obese women being 16% to 50% more likely to experience depression, reinforcing the cycle of poor nutrition, obesity, and MH disorders. So, the study concludes that improving nutritional quality may be a crucial intervention for enhancing mental health among obese females, underscoring the importance of integrated approaches to address both physical along with mental health in this population.